Penyelesaian Kredit Macet Terkait Adanya Tagihan Utang Pajak Debitur di Bank BRI Kantor Cabang Medan Thamrin - Arfandi, Muhammad; Ginting, Budiman; Barus, Utary Maharany; Siahaan, Rudy Haposan (Mahesa Research Center, 2024)
The implementation of mortgage execution, execution (parate execution) must be based on a promise to sell under one's own power as regulated in Article 1178 paragraph (2) of the Civil Code, so that it is an implementation of an agreement and accompanied by a mortgage deed grosse which is intended